Agathocles' Self-Representation as a Counterpart to Alexander in Syracusan Coinage: Doriktetos Chora, Athena, Artemis and Heracles - Marco Vitale (Gerión)
Do self-proclaimed royal successors, so-called "Diadochi", of Alexander the Great appear exclusively in the mammoth empires he left behind? Egypt, Asia Minor, Babylonia, Macedonia, Greece? Just people like Ptolemy, Seleucus, Lysimachus, Cassander, Demetrius? No. At least in terms of power staging and according to historical narratives of the Hellenistic and Roman periods, regular Diadochi and emulators of Alexander can even be identified in far-off Sicily. In particular, the first official king of Syracuse and contemporary of Alexander, Agathocles, adopted significant elements of Alexander's ancient Oriental-Macedonian self-portrayal and hybridised them with the local Sicilian pictorial tradition to create interesting and original new creations, which we will examine on the basis of Syracusan coins and ancient literature.